Development and preliminary validation of a mandarin Chinese language questionnaire measuring betel quid dependency among adults in Taiwan. (January 2019) - Tsai, Ming-Hsui; Li, Tsai-Chung; Li, Chia-Ing; Gritz, Ellen R.; Lam, Cho; Chiu, Chang-Fang; Liu, Chiu-Shong; Lai, Chien-Chen; Hsu, Wei-Yi; Tamí-Maury, Irene; Lu, I-Ying; Lin, Cheng-Chieh
Highlights: The Chinese-version BQDI, measuring betel quid dependence that is theoretically anchored in the framework of substance dependence guided by WHO and DSM-IV-TR for improving content validity, has been validated in 113 participants. BQDI scores consisted of a three-factor structure, including physical and psychological urgent need, lack of resistance to betel quid, and maladaptive use. The significant cross-sectional association between BQDI scores and arecaidine and N-methylnipecotate support the construct and discriminatory ability of BQDI. Abstract: The purposes of this study were to develop the Chinese-version betel quid dependence instrument (BQDI) and to test its reliability and validity. An item pool relevant to betel quid dependence was generated. A panel of three experts assessed content validity including content relevance, clarity, and domain coverage. A cross-sectional study was conducted, consisting of 113 participants from a construction site, betel quid stalls, and a teaching hospital in Taichung, Taiwan. Construct validity was assessed by hypothesizing a significant correlation between the BQDI score and number of pieces-years for betel quid chewing and betel quid biomarkers. The overall Cronbach's alpha coefficient was 0.94. Factor analysis indicated the BQDI consisted of a three-factor structure, including physical and psychological cravings, lack of resistance to betel quid, and maladaptive use. We observed significant associations of BQDI total and factor scores with arecaidine (adjusted odds ratio [OR] for medium total BQDI score: 12.87, 95% CI: 1.45–114.5; high total BQDI score: 28.9, 3.53–236.6) and N-methylnipecotate (medium total BQDI score: 6.18, 1.21–31.62; high total BQDI score: 13.10, 2.72–63.03, respectively). Our results provide preliminary good internal consistency and construct validation of the Chinese-version BQDI as a measure of betel quid dependence in community adults.